Exploring the short-term impact of community water fluoridation cessation on children's dental caries: a natural experiment in Alberta, Canada. (May 2017) - McLaren, L.; Patterson, S.; Thawer, S.; Faris, P.; McNeil, D.; Potestio, M.L.; Shwart, L.
Abstract: Objectives: Dental caries (tooth decay) is common and can be serious. Dental caries is preventable, and community water fluoridation is one means of prevention. There is limited current research on the implications of fluoridation cessation for children's dental caries. Our objective was to explore the short-term impact of community water fluoridation cessation on children's dental caries, by examining change in caries experience in population-based samples of schoolchildren in two Canadian cities, one that discontinued community water fluoridation and one that retained it. Study design: We used a pre-post cross-sectional design. Methods: We examined dental caries indices (deft [number of decayed, extracted, or filled primary teeth] and DMFT [number of decayed, missing, or filled permanent teeth]) among grade 2 schoolchildren in 2004/05 and 2013/14 in two similar cities in the province of Alberta, Canada: Calgary (cessation of community water fluoridation in 2011) and Edmonton (still fluoridated). We compared change over time in the two cities. For Calgary only, we had a third data point from 2009/10, and we considered trends across the three points. Results: We observed a worsening in primary tooth caries (deft) in Calgary and Edmonton, but changes in Edmonton were less consistent and smaller. This effect was robust to adjustment for covariates available in 2013/14 and was consistent with estimates of total fluoride intake from biomarkers from a subsample. This finding occurred despite indication that treatment activities appeared better in Calgary. The worsening was not observed for permanent teeth. For prevalence estimates only (% with >0 deft or DMFT), the three data points in Calgary suggest a trend that, though small, appears consistent with an adverse effect of fluoridation cessation. Conclusions: Our results suggest an increase in dental caries in primary teeth during a time period when community fluoridation was ceased. That we did not observe a worsening for permanent teeth in the comparative analysis could reflect the limited time since cessation. It is imperative that efforts to monitor these trends continue. Highlights: There is limited research on cessation of fluoridation and children's dental health. Fluoridation cessation is occurring with increasing frequency in some regions. Decision-makers in those regions have limited evidence to inform policy decisions. We explored children's dental health in a cessation community and a comparison community. Dental caries in primary teeth increased to a greater extent in the cessation community.